Dinamika Populasi, Sampel, Dan Kredibilitas Sumber Ilmiah: Kontribusinya Terhadap Mutu Penelitian Akademik Era Digital - Maritasari, Donna Boedi; Ermayani, Eli; Sapitri, Halda Aulia Asmia; Hidayat, Masykur (CT. Rajawali media Utama, 2025)
In research activities, it is important for a researcher to understand how to identify populations and select the right samples so that the data collected actually represents reality. In addition, the source of information used must also be completely reliable in order for research results to be valid and not misleading. In a digital age like today, the ease of access to information on the Internet brings new challenges. Much information is available, but not all of it comes from reliable sources. Therefore, this article discusses how populations, samples, and the credibility of information sources play a role in improving the quality of academic research. Using a library review approach from various journals and books published over the past five years, this article aims to provide a comprehensive and practical picture for researchers, particularly students and academics.